Taste and Hypertension in Humans: Targeting Cardiovascular Disease - Roura, Eugeni; Foster, Simon; Winklebach, Anja; Navarro, Marta; Thomas, Walter; Campbell, Katrina; Stowasser, Michael (Current Pharmaceutical Design, 2016)
The association between salty taste and NaCl intake with hypertension is well-established, although it is far from completely understood. Other taste types such as sweet, umami or bitter have also been related to alterations in blood pressure. Here, we review the mutual relationship between taste and hypertension to identify potential avenues to better control blood pressure. This review focuses on published data involving humans, with the exception of a section on molecular mechanisms. There is compelling evidence to suggest that changes in salty taste sensitivity can be used to predict the onset of hypertension. This goes hand in hand with the medical concept of sodium sensitivity, which also increases with age, particularly in hypertensive patients. The association of hypertension with the loss of taste acuity less definitive with some data/conclusions masked by the use of anti-hypertensive drugs. In fact, this group of therapeutic agents can reduce food taste perception resulting in mild to severe hypogeusia and dysgeusia. In the elderly, antihypertensive drugs may lead to a loss of appetite, thus, selecting treatments with low or no impact on taste perception should be advised. Pharmacological approaches to mitigate cardiovascular disease (CVD) could well take a different spin in the future following the discovery of taste receptors (TAS1R and TAS2R) in the cardiovascular system. Finally, long-term dietary strategies to minimize the risk of development of hypertension and CVD are discussed identifying several nutrients and public health policies with relevant potential.
Keywords: CVD